Tinjaun Pelayanan dalam Birokrasi: Studi Kasus pada Dinas Kependudukan dan Catatan Sipil Kabupaten Bireuen - Mawaddah Mawaddah (Singkite Journal, 2025)
Bureaucracy ideally functions as a public servant that ensures order, speed, and transparency. However, bureaucracy at the local level is often perceived as slow, complicated, and unprofessional, ultimately reducing public trust and hindering prosperity. This study aims to review and identify service delivery and analyze the causal factors. The study was conducted at the Population and Civil Registration Service (Disdukcapil) of Juang City, Bireuen Regency, as a case study. Using a qualitative approach, data was collected through in-depth interviews, observation, and documentation. The results revealed crucial problems including allegations of illegal levies (pungli), delays in document issuance due to a shortage of raw materials, a non-transparent queuing system, low employee ethics and friendliness, and limited infrastructure and technology. The main contributing factors are lack of leadership supervision, low employee discipline, and an unresponsive old bureaucratic culture. Therefore, it is time for bureaucratic reform, particularly improving discipline and strengthening service ethics.